Review: The Decline of Christendom in Western Europe, 1750–2000 - Kent, John (The journal of theological studies, 2004)
The Decline of Christendom in Western Europe, 1750–2000 Hugh McLeod Werner Ustorf Pp. x + 234 Cambridge Cambridge University Press 2003 0 521 81493 6 £40/$60